GE_GERICHTE C/20803/2010 vom 28. Juni 2013 - GE Cour de justice (2013)
DIVORCE; AUTORITÉ PARENTALE; DROIT DE GARDE; ADMINISTRATION DES PREUVES; OBLIGATION D'ENTRETIEN | CPC.316.d.3; CC.133; CC.273.1; CC.274; CC.276; CC.285